(untitled) (Acta Scientiarum. Health Sciences, 2019)
The present study compared the acute effect of different combinations of resistance training (RT) and static stretching (SS) on the heart rate (HR), rate pressure product (RPP) and oxygen saturation (SpO2) of participants. This is a cross-over methodological design carried out in five visits on non-consecutive days, which always occurred at the same time of day. Twelve trained young men were randomly divided, using counterbalanced and alternate assignments, into three experimental situations: a) horizontal abduction of the shoulder, knee flexion and hip abduction before the bench press and leg extension machine, respectively (SS + RT); b) bench press and leg extension machine before horizontal abduction of shoulder, knee flexion and hip abduction, respectively (RT + SS); c) bench press and leg extension machine, exclusively (RT). Analysis of variance (ANOVA) with repeated measures showed significant differences in the SS+RT group when the variables were compared at rest (pre) and immediately after the exercises (post): HRpre vs. HRpost (p = 0.000) and RPPpre vs. RPPpost (p = 0.000). In the intergroup comparisons, significant differences were detected between the SS+RT and RT+SS experimental situations exclusively during the post period for the RPP (p = 0.041) and SpO2 variables (p = 0.002). The combined use of SS and RT significantly changed the intragroup cardiovascular responses by increasing the HR and RPP and decreasing the SpO2. However, the values were lower in the intergroup comparisons when the stretching exercises were performed both before and after RT, although no significant differences were found from a cardiovascular safety point of view.